The implications of face masks for babies and families during the COVID-19 pandemic: A discussion paper. Issue 1 (February 2021) - Green, Janet; Staff, Lynette; Bromley, Patricia; Jones, Linda; Petty, Julia
Abstract: COVID-19 has changed the way that newborn babies are cared for within the neonatal setting due to the introduction of social distancing and wearing of face masks to limit the spread of the infection. Potential implications exist related to the normal development of bonding and connections with others. This paper discusses the importance of face to face interactions for early attachment between babies and parents within the context of relevant underpinning developmental theory. Mask wearing can also potentially impact relational communication, requiring us to change our current ways of working. Decreasing face to face interactions and relational communication, along with key recommendations for both parents and health professionals are further highlighted to mitigate the potential negative effects of masks on long-term development related to human connection and attachment.